Development and validation of an instrument for evaluating the ludicity of games in health education - Maria Raquel Gomes Maia Pires; Leila Bernarda Donato Göttems; Laianna Victoria Santiago Silva; Paloma Aparecida Carvalho; Gislane Ferreira de Melo; Rosa Maria Godoy Serpa da Fonseca (SciELO, 2015)
Abstract OBJECTIVE Developing and validating an instrument to evaluate the playfulness of games in health education contexts. METHODOLOGY A methodological, exploratory and descriptive research, developed in two stages: 1. Application of an open questionnaire to 50 graduate students, with content analysis of the answers and calculation of Kappa coefficient for defining items; 2. Procedures for construction of scales, with content validation by judges and analysis of the consensus estimate byContent Validity Index(CVI). RESULTS 53 items regarding the restless character of the games in the dimensions of playfulness, the formative components of learning and the profiles of the players. CONCLUSION Ludicity can be assessed by validated items related to the degree of involvement, immersion and reinvention of the subjects in the game along with the dynamics and playability of the game.